(untitled) (Herald of Journalism, 2022)
The research developed the attitude to the publication in the media like to the channel of informatiza- tion of entrepreneurship and private business. The training program in journalism should addresses the de- velopment of business also. Entrepreneurship needs not only a management or economic system, but also information. Curricula in journalism education should offer training based on professional experience, and students should be able to consider not only their field, but also part of the entrepreneurship. By informing the student must be able to achieve high results so that a particular product will be in demand in the market. The main purpose of the research is to establish a link between entrepreneurship and private busi- ness media. Entrepreneurship in our country is considered just as a system of economic relations in the administrative system. As a scientific method, the content analysis of articles on this topic, research on the legislation «On support and protection of private entrepreneurship» and thematic analysis were used. According to the results of the research in the current situation scientists identify the entrepreneur as a subject of search and implementation of new opportunities for the introduction of new ideas, develop- ment of new technologies, innovation, application of new customer service and development of new areas of capital. The state of informatization of business has a positive effect on the economic direction. In the market conditions the entrepreneur decides what goods and services consumers will need tomorrow, and needs the correct delivery of information about those goods. A properly structured media publication policy can contribute to this. Key words: entrepreneurship, private business, economics, media, advertising.